Implementasi Kurikulum Merdeka Belajar pada Mata Pelajaran Akidah Akhlak di Kelas X MIA Madrasah Aliyah Hidayatul Mubtadiin Jati Agung Lampung Selatan - Siti Nurhasanah (Journal on Education, 2024)
The independent curriculum is implemented at Madrasah Aliyah Hidayatul Mubtadiin in the 2023/2024 academic year. This study aims to analyze: (1) the implementation of the independent learning curriculum in the subject of faith and morals in class X MIA Madarasah Aliyah Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung. (2) What are the obstacles faced and solutions to the implementation of the independent curriculum in the subject of faith and morals in class X Mia Madarasah Aliyah Hidatul Mubtadiin Jati Agung South Lampung. This type of research is descriptive qualitative which was carried out at Madrasah Aliyah Hidayatul Mubtadiin Jati Agung South Lampung. The subjects in this study were the subject teachers of Faith and Morals and students in class X. Data collection techniques used observation, interview, and documentation methods. The data validity technique used source triangulation. The data analysis technique uses interactive analysis through four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) The implementation of the independent learning curriculum in the subject of faith and ethics in class X MIA Madrasah Aliyah has 3 stages, namely planning, implementation and evaluation. (2) Obstacles faced and solutions in the implementation of the independent learning curriculum in the subject of Faith and Ethics in class X Madrasah Aliyah Hidayatul Mubtadiin obstacles faced are the lack of teacher knowledge about the implementation of the independent curriculum, difficulty in determining learning strategies and methods, limited student books, teaching materials that are too broad, and limited internet. solutions to these obstacles, teachers write and explain the material on the board, students take notes, and teachers prepare student worksheets, and teachers look for information about the implementation of the independent curriculum.